2014
DOI: 10.1089/lgbt.2013.0047
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes About Preexposure Prophylaxis (PrEP) Among Sexually Active Men Who Have Sex with Men and Who Participate in New York City Gay Pride Events

Abstract: We conducted a street-based intercept survey with 480 men reporting sex with men (MSM) during June 2011 Gay Pride events in New York City (NYC). Awareness and knowledge of pre-exposure prophylaxis (PrEP) were limited. Many men believed that PrEP use should be encouraged, and that some of their friends would use it; and were interested in using it themselves. Men who believed that PrEP should only be taken before sex were more likely to endorse it and report greater likelihood of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…First, we used a convenience sample from a single mobile dating application, which may not be representative of all MSM in the Bronx, and findings may not be generalizable to other MSM communities. However, we found similar rates of PrEP awareness in other studies in New York City using different recruitment approaches (Grov et al, 2016; Mantell et al, 2014; Rucinski et al, 2013). Additionally, a prior in-person survey of Bronx MSM found widespread use of social media, with individuals using online dating applications having higher rates of risk behaviors (Patel et al, 2016), suggesting we reached a population that could benefit from PrEP.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…First, we used a convenience sample from a single mobile dating application, which may not be representative of all MSM in the Bronx, and findings may not be generalizable to other MSM communities. However, we found similar rates of PrEP awareness in other studies in New York City using different recruitment approaches (Grov et al, 2016; Mantell et al, 2014; Rucinski et al, 2013). Additionally, a prior in-person survey of Bronx MSM found widespread use of social media, with individuals using online dating applications having higher rates of risk behaviors (Patel et al, 2016), suggesting we reached a population that could benefit from PrEP.…”
Section: Discussionsupporting
confidence: 87%
“…Compared to other studies reporting on PrEP awareness in New York City MSM, which recruited using different approaches (in-person, bars, bathhouses, or via MSM specific Internet websites) and conducted prior to (Mantell et al, 2014; Rucinski et al, 2013) or after FDA approval of PrEP (Grov, Rendina, Whitfield, Ventuneac, & Parsons, 2016), rates of PrEP awareness were similar to that in our sample, ranging from 28% to 38.8%. Our findings may not be that surprising, given that this study was conducted just over 1 year after FDA approval of PrEP and the average time for new health care innovations to become widely known and adopted can be considerably long, as a more recent study of PrEP use in Black MSM found continued minimal awareness and thus stalled uptake (Eaton, Driffin, Bauermeister, Smith, & Conway-Washington, 2015).…”
Section: Discussionsupporting
confidence: 57%
“…Although recent studies have examined PrEP knowledge and interest among MSM at social events (Eaton et al, 2014; Mantell et al, 2014), a logical next question in PrEP implementation is whether community outreach and engagement among MSM translates into actual PrEP utilization. Implementation across the US is proceeding on different fronts in clinical settings and community-based organizations, and also should be furthered through advocacy, public health projects and community outreach (Hosek, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward PrEP and its uptake in MSM have varied widely, and awareness of its availability has increased with time (Bauermeister, Meanley, Pingel, Soler, & Harper, 2013; Grov, Whitfield, Rendina, Ventuneac, & Parsons, 2015; Mantell et al, 2014). The only study to date to examine the awareness, use, and acceptability of PrEP specifically among app users found that only 1.6% of a sample of 375 Grindr users in Los Angeles had taken PrEP (Landovitz et al, 2013).…”
mentioning
confidence: 99%